HEART, HEAD AND HAND: THEOLOGY AND BATIK INDUSTRY IN NATION BUILDING FOR DEVELOPING COUNTRY - Imam Khanafi; Susminingsih Susminingsih (Islam Futura, 2020)
This paper focuses on analyzing the implementation of theology in the batik industry in the process of nation building in Indonesia as a developing country. Religion becomes a code of conduct for the Indonesians. This research has a question how theology which has noble values for humanity, makes the batik industry more meaningful, boarderless and cross culture by involving various ethnicities and interfaith; Javanese, Arabic and Chinese, Muslim and non-Muslim. This study uses qualitative methods to draw data and analyze it descriptively-philosophically-sociologically. Observation, interview and documentation are the data collection techniques from primary and secondary sources. This study found that 1) theology and industry actually have a symbiotic relationship to show their respective roles in industry profiles aimed at increasing humanity, 2) through theology, the Pekalongan batik industry has changed the way humans view the meaning of work, that through theology, actors the batik industry has in fact moved their hearts, minds and deeds in creating working relationships, motives and environments both the surrounding community and the nation and country, 3) nation building in Indonesia as a developing country has unique characteristics, because the Indonesian people have a variety of cultures that are closely related with spirituality values.